Dishonorable Intentions: Stone Barrington #38 - Woods, Stuart (New York : G.P. Putnam's Sons, 2016)
"Stone Barrington gains an adversary that he can't seem to shake in the electrifying new adventure from the #1 New York Times-bestselling author. Stone Barrington's latest lady friend is full of surprises, both good and ill. A sensual woman with unexpected desires, Stone finds her revelations in the boudoir extremely agreeable. But on the other hand, she also has some unfinished business with a temperamental man who believes Stone is an intolerable obstacle in the way of his goals. In a cat-and-mouse game that trails from sun-drenched Bel-Air to a peaceful European estate and the wild New Mexican desert, Stone and his friend remain just one step ahead of their opponent. But their pursuer is not a man who can stand to be thwarted, and tensions are mounting. and may soon reach the boiling point"--.
Keywords: Barrington, Stone (Fictitious character) -- Fiction; Private investigators -- Fiction; FICTION / Suspense; FICTION / Thrillers; FICTION / Action & Adventure; Suspense fiction; Adventure fiction